Key technologies for polymer electrolyte membrane fuel cell systems fueled impure hydrogen - Pei, Pucheng; Wang, Mingkai; Chen, Dongfang; Ren, Peng; Zhang, Lu (Progress in natural science, 2020)
Hydrogen energy and polymer electrolyte membrane (PEM) fuel cells become concerned issues in recent years. Nevertheless, the construction of hydrogen refueling infrastructure and hydrogen storage and transportation constrains the commercial development of fuel cells. In this review, sources, production, storage, transportation, and purification methods of hydrogen are extensively reviewed and compared. The advantages of utilizing industrial by-product hydrogen and steam reforming gas in PEM fuel cell systems are analyzed. Using industrial wasted hydrogen can significantly reduce the cost of hydrogen. Also, it is indicated that the onboard hydrogen generation by steam methanol reforming can solve the difficulties of efficient storage and transportation of gaseous hydrogen, which means that methanol has great potential to be a convenient carrier of hydrogen. The effects of impurities contained in the reformate gas are generally introduced. After the methanol steam reforming and pretreatment purification processes, the reformate gas can be fed to PEM fuel cells. Thus, a fuel cell system integrated with onboard hydrogen production and impure hydrogen treatment subsystems is introduced, and key technologies therein for pretreatment purification and in-situ poisoning mitigation methods are reviewed. Finally, suggestions are proposed for further studies. [Display omitted] •H2 production, storage, and transportation methods are introduced and compared.•Utilizing impure H2 and fuel reforming reduce H2 cost and solve pain points of H2 storage and incomplete infrastructure.•Key technologies for impure H2 utilization are reviewed in terms of PEM fuel cell system applications.•A PEM fuel cell system integrated with onboard SMR and PROX is promising to facilitate hydrogen energy development.•Further studies regarding material science and technology related to this field are suggested.